Study on Implementation of Special Efforts to Increase Production of Rice, Corn, Soy (Upsus Pajale) in Cakranegara District, Mataram City - Ajeng Kartika Pratiwi; Muktasam Muktasam; Dian Lestari; Taslim Sjah (IKIP Mataram, 2022)
The Special Effort Program to Increase Rice, Corn and Soybean Production (Upsus Pajale) is a program to increase food production in 2015 which was implemented in Indonesia, including in Cakranegara District, Mataram City. With the implementation of the program, the purpose of this research is to analyze the level of implementation, identify obstacles and supports of the Upsus Pajale program which concentrates on rice commodities in Cakranegara District, Mataram City. This study uses descriptive methods and data collection techniques with survey techniques. The sampling technique used in the sampling area was purposive sampling (deliberately) with the consideration that 2 sub-districts received the Upsus Pajale program. The technique of determining the number of respondents used proportional sampling so that 40 respondents were determined according to the number of sub-populations of farmer groups in 2 villages in Cakranegara District. The data analysis used is categorical and descriptive data analysis. The results showed that there were 3 main stages in the implementation of the Upsus Pajale program, namely the planning stage was achieved well (62.5%), the implementation stage (97.5%), and the evaluation stage was achieved less well (80%). The Upsus Pajale sub-program that was well implemented in Cakranegara sub-district included 100% Irrigation Network Development, Land Optimization (100%), and System of Rice Intensification (95.2%). Constraints faced during program implementation include natural and technical constraints. Supporters of the program are Agricultural Field Extension Officer, Babinsa, assistant students from the Faculty of Agriculture, University of Mataram, and activities from farmer groups.